A Grief Observed - Lewis C. S (Faber And Faber, 1961)
Begun after his wife's death from a long and painful illness the journal might itself have been an instrument of escape. But its honest dissection is the negation of self-pity. Honest it is; but too complex, intellectualized and indeed well-written to be artless in the sense of naive. Drawing firmly back from each conventional posture of the mourner, C. S. Lewis invites not sympathy but co-operation in his attempt to argue out a grief.